Effects of curry (Murraya koenigii spreng.) leaf extract on the microbial and physico-chemical qualities of yellow alkaline noodles during storage - Rosyid, Teza Alfindo (2012)
Yellow alkaline noodles (YAN) are very susceptible to spoilage due to the high pH ,and high moisture content of the product. The present study was conducted in an attempt to improve the shelf life of YAN using natural preservatives from local leaf extracts. This study involved the isolation and identification of the spoilage bacteria using the Biolog GEN III, screening of antibacterial activity of six types of local leaves on the identified bacteria followed by storage quality study of YAN treated with the most effective of leaf extracts. In the first part of this study, eight bacteria were identified out of thirty colonies that were isolated. Five were Gram-positive (GP) bacteria which include Bacillus pumilus, Clavibacter agropyri, Corynebacterium urealyticum, Corynebacterium jeikeium and Staphylococcus sciuri, and three were Gram-negative (GN) bacteria Enterobacter cloacae, Pseudomonas aeruginosa and Serratia marcescens. The E. cloacae and S. sciuri were found to be the most abundant bacteria on YAN with percentage of occurrence from all of thirty identified isolates at 23% and 26%, respectively. In the second part of the study, six local leaf extracts which were 'Pegaga' (Centella asiatica) 'Melur' (Jasminum sambac), 'Jarum tujuh bilah' (Pereskia bleo), 'Ulam raja' (Cosmos caudatus), 'Curry' (Murraya koenigii) and 'Tenggek burung' (Melicope lunu) were screened for their antibacterial activity against the identified bacteria in YAN. The agar disc-diffusion method was employed in the determination of antibacterial activities of organic and aqueous extracts. Generally, all the leaf extracts studied showed the presence of certain levels of antibacterial activity against identified bacteria in YAN. Leaf extracts of curry (M koenigii) was discovered to possess effective antibacterial activity against GP and GN bacteria in YAN as compared to other leaf extracts. The observed inhibition zone diameter (IZD) of organic extracts was in the range of 6.90 to 20.63 mm, whereas for aqueous extracts was between 6.43 to 14.45 mm. Tetracycline which was used as positive control (standard antibiotic) showed the highest IZD against GP and GN bacteria tested at i.e. in the range of 17.0 to 25.67 mm. Result of the study showed that curry leaf extracts had the most effective antibacterial activity on the storage quality of YAN in an effort to extend the shelf life by using a natural preservative. Treated YAN were prepared by adding 0.5 % of organic leaf extracts of curry, while the untreated YAN (control) was prepared without the addition' of leaf extracts. The noodle samples were stored at ambient temperature (28±2°C) for six days and at chilled temperature (4±2°C) for six weeks. The microbiological qualities (total aerobic mesophilic bacteria, psychrophilic bacteria, yeast and mould count) physico-chemical properties (hardness, adhesiveness, springiness, cohesiveness, resilience, moisture con tent, pH value, and colour characteristic) of both samples were analysed. The leaf extracts of curry was found to significantly (P<0.05) reduced the initial load of total aerobic mesophilic bacteria, psychrophilic bacteria and yeast and mould count in noodle at ambient and chilled temperatures. The textural property of treated YAN was significantly (P<O.05) affected by the addition of curry leaf extracts. Significant (P<0.05) changes on moisture content and pH value were observed in the samples, with treated having a lower values as compared to the control YAN. In term of colour measurement, both of control and treated YAN showed a significant (p<0.05) reduction in colour parameters during storage at both temperatures. Shelf life of treated YAN at ambient and chilled temperatures were extended to 5 and 5 weeks, respectively, while, the shelf life of control YAN at ambient and chilled temperatures were 1.5 days and one week, respectively. This finding implied that bioactive compound of the curry leaf extracts can be used to extend the shelf life with combination of chilled condition further improves the storage stability of YAN. The combination of this preservation with chilled condition could further improve the YAN shelf life.